Lymphocyte Proliferation Activity MTT -Test of Ethanolic Extract of Pasak Bumi Root (Eurycoma longifolia Jack) on Induced 7,12-Dimethylbenz[A] Antracene (DMBA) Female Sprague Dawley Rat - Falah, Lily Noor; Yuliani, Sapto (Indonesian Research Gateway, 2011)
Pasak bumi root (Eurycoma longifolia Jack) contains quasinoid. Quasinoid potentially hasÃÂ antitumor/anticancer,ÃÂ anti-parasitic,ÃÂ andÃÂ immunostimulatoryÃÂ activity.ÃÂ TheÃÂ aimÃÂ ofÃÂ this research was to study the lymphocyte proliferationÃÂ activity MTT-testÃÂ ÃÂ of ethanol extract ofÃÂ EurycomaÃÂ longifoliaÃÂ JackÃÂ rootÃÂ onÃÂ inducedÃÂ byÃÂ 7,12-dimethylbenz[a]ÃÂ antraceneÃÂ (DMBA) female Sprague Dawley rat. The test was done at 6 groups of 10ÃÂ SD rat each. Each groups wasÃÂ administeredÃÂ orallyÃÂ withÃÂ DMBAÃÂ (GroupÃÂ I)ÃÂ ÃÂ ÃÂ doseÃÂ ofÃÂ 20 mg/kgÃÂ bw,ÃÂ corn oilÃÂ (GroupÃÂ II), baseline (Group III), andÃÂ ethanol extract of pasak bumi root dose 12.6; 25.2; and 50.4 mg/kg bw (Group IV,V,and VI). Ethanol extract is given for 5 weeks. At the second week five rats wereÃÂ sacrificedÃÂ toÃÂ isolateÃÂ theÃÂ lymphocytesÃÂ ofÃÂ spleenÃÂ thenÃÂ ratsÃÂ areÃÂ injectedÃÂ orallyÃÂ with DMBA 2 times a week for 5 weeks. At the eight until twenty fourth week all groups were justÃÂ administeredÃÂ byÃÂ aquades.ÃÂ MeasurementÃÂ ofÃÂ spleenÃÂ relativeÃÂ weightÃÂ andÃÂ isolationÃÂ ofÃÂ the lymphocyteÃÂ spleenÃÂ wereÃÂ doneÃÂ atÃÂ secondÃÂ weekÃÂ andÃÂ theÃÂ lastÃÂ ofÃÂ experiment.ÃÂ Lymphocyte proliferationÃÂ activityÃÂ wereÃÂ measuredÃÂ byÃÂ MTT-reductionÃÂ method.ÃÂ DataÃÂ wereÃÂ analyzed statisticallyÃÂ byÃÂ analyzesÃÂ ofÃÂ varianceÃÂ (anova)ÃÂ continuedÃÂ byÃÂ ÃÂ ÃÂ ÃÂ ÃÂ LSDÃÂ testÃÂ andÃÂ KruskallÃÂ Wallis continued by Mann Whitney test. The result showed that limphocyte proliferation activity MTT of ethanol extract of E. longifolia root doses of 12.6; 25.2; and 50.4 mg/kg bw for 14 days prior to DMBA-induced areÃÂ 339.35 ÃÂ± 8.43;61.20 ÃÂ± 6.27;ÃÂ 310.28 ÃÂ±ÃÂ 6.81ÃÂ ÃÂ andÃÂ dose 50,4 mg/kg bw afterÃÂ DMBA-induced is 122.108 ÃÂ±ÃÂ 11.426